Pengembangan Strategi Perbaikan Kualitas Layanan Taman Hiburan Dunia Fantasi Ancol - Ronald Sukwadi; Wahyuni Inderawati; Vincent Lie (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
As a recreational place, the amusement park provides entertainment to both domestic and foreign visitors. One of well-known amusement parks in Indonesia is Dunia Fantasi Ancol (Dufan) Jakarta. The objective of this study is to analyze the amusement park visitors’ perception in order to assist the development of improvement strategic plans. The refined Kano 's model and Importance Performance Analysis (IPA) method were applied. Based on data obtained from 272 visitors, there are 18 service attributes that affect the performance of Dufan: 8 attributes have excellent performance levels, 5 attributes have surplus performance levels, and 5 attributes should be improved. Finally, based on Blue Ocean Strategy model, nine improvement strategies and also proposed canvas strategy were provided.Keywords: Amusement park, service attributes, refined Kano’s model, IPA, Blue Ocean Strategy.